Comparative analysis of opioid use between robotic and open pancreatoduodenectomy. (15th July 2022) - Witt, Russell G.; Hirata, Yuki; Prakash, Laura R.; Newhook, Timothy E.; Maxwell, Jessica E.; Kim, Michael P.; Tran Cao, Hop S.; Lee, Jeffrey E.; Vauthey, Jean‐Nicolas; Katz, Matthew H. G.; Tzeng, Ching‐Wei D.; Ikoma, Naruhiko
Abstract: Background/Purpose: Risk‐stratified pancreatectomy clinical pathways using regional anesthesia and multimodality analgesia have decreased overall opioid use, but the additional benefits of robotic surgery in opioid reduction for pancreatoduodenectomy (PD) are unknown. We compared the inpatient opioid use between robotic PD and open PD. Methods: Patients undergoing open PD within a protocol evaluating preincisional regional anesthetic block bundles were compared to consecutively‐treated patients undergoing robotic PD identified from a prospectively maintained single‐institutional database. Clinical characteristics, operative outcomes, pain scores and inpatient oral morphine equivalent (OME) use were compared between patients treated with robotic or open PD. Patients with a history of continuous‐release opioid dependence were excluded. Results: Of 114 total patients, 25 underwent robotic PD and 89 underwent open PD. Intraoperative opioid use was not different ( P = .87), nor were cumulative pain scores. Robotic PD patients used significantly fewer OMEs per day on postoperative days 1–4 ( P = .039), used fewer total OMEs during hospitalization (robotic: median = 79, IQR 42.5–141; open: median = 126, IQR 61.3–203.8; P = .0036) and were discharged with fewer OMEs (robotic: median = 0, IQR 0–43.8; open: median = 25, IQR 0–75; P = .009) despite a shorter length of stay (robotic: median = 4, open: median = 5, P = .002). Conclusions: Robotic PD patients required fewer inpatient OMEs than open PD while maintaining similar pain scores. A higher percentage of robotic PD patients tapered off of opioids prior to discharge than open surgery patients treated with a standardized opioid reduction protocol despite a shorter length of stay. These results provide a rationale for choosing robotic PD when feasible to minimize opioid use. Abstract : Witt and colleagues compared opioid use and short‐term outcomes of robotic and open pancreatoduodenectomy. Robotic pancreatoduodenectomy patients required fewer inpatient opioids and included a higher percentage of patients tapering off of opioids prior to discharge than their open surgery counterparts despite a shorter length of stay and similar complication rate.